1995
DOI: 10.1071/ea9951015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soil biological properties as potential bioindicators of soil health

Abstract: Two long-term field trials in South Australia were used to detect and characterise changes in soil biological properties that were a consequence of different agricultural management. The properties examined were total bacteria, fungi, and actinomycetes; total pseudomonads; cellulolytic bacteria and fungi; mycorrhizal fungi; plant root pathogens (Gaeumannomyces graminis var. tritici, Rhizoctonia solani, Pythium irregulare); bacterial-feeding protozoa; soil mesofauna (collembola and acari); earthworms; microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(85 citation statements)
references
References 37 publications
5
74
1
5
Order By: Relevance
“…Additionally, these constraints do not appear to be consistently affected by management, other than a suggestion that effects are greater in cropped soils. This is contrary to the findings for major diseases like crown rot (Wildermuth et al 1997), take-all (Rovira 1990), Pythium root rot (Pankhurst et al 1995), and Rhizoctonia bare patch (Neate 1987).…”
Section: Discussioncontrasting
confidence: 55%
“…Additionally, these constraints do not appear to be consistently affected by management, other than a suggestion that effects are greater in cropped soils. This is contrary to the findings for major diseases like crown rot (Wildermuth et al 1997), take-all (Rovira 1990), Pythium root rot (Pankhurst et al 1995), and Rhizoctonia bare patch (Neate 1987).…”
Section: Discussioncontrasting
confidence: 55%
“…Soil microbial biomass is defined as an indicator of soil fertility and quality, which is easily influenced by soil managements (Pankhurst et al 1995). Wang et al (2004) reported that an application of chemical fertilizers (NPK) increased the black soil MBC compared with no fertilization, and reached the same level as the natural restoration in soil layer of 0-20 cm.…”
Section: Discussionmentioning
confidence: 97%
“…Como possuem relação direta com as condições de solo, qualquer alteração no ecossistema afetará a densidade, diversidade e a atividade das populações microbianas do solo (Pankhurst et al, 1995). O carbono na biomassa microbiana é o destino inicial do carbono que será transformado no solo e funciona como energia armazenada para processos microbianos e, por responder rapidamente às alterações no solo, pode ser usado como identificador de alterações na matéria orgânica do solo em curto prazo (Rice et al, 1996). A relação entre o carbono da biomassa e o carbono orgânico total demonstra processos importantes relacionados com aportes e transformações da matéria orgânica, assim como a eficiência de conversão do carbono desta em carbono microbiano (Sparling, 1992).…”
Section: Introductionunclassified